Aphid Species, Their Natural Enemies in Vegetables from Erzincan, Turkey: First Record of the Parasitoid Wasp Aphelinus mali (Haldeman) parasitizing Lipaphis erysimi (Kaltenbach)* - İsmail Alaserhat; Adnan Canbay; İşıl Özdemir (Journal of Agricultural Sciences)
Aphid species, their parasitoids and predators on vegetables (bean, cucumber, eggplant, melon, okra, pepper, pumpkin, tomato and watermelon) grown in Erzincan province, Turkey were determined. Surveys were carried out at weekly intervals from the seedling period until the end of the harvest period in Central and Üzümlü districts of Erzincan province in 2014-2016. 30-40 plants were randomly selected in the surveys and all parts of plants were investigated with a magnifier. Ten aphid, seventeen predator and seven parasitoids species were found. According to results, Lipaphis erysimi (Kaltenbach) (Hemiptera: Aphididae) was first recorded as a host of Aphelinus mali (Haldeman) (Aphelinidae: Aphelininae) in the world. In addition, parasitism rates of aphids were also established. The mean parasitism rate changed between 17.5% in 2015 and 4.39% in 2016. The relationship between parasitism rate, total parasitized aphid number and total aphid number were found. According to the analysis result, there was a very weak or a high positive correlation (r= 0.126-0.721) between total aphid number and total parasitized (mummified) aphid number, and not a correlation existed between parasitism rate and total aphid number as for years.